Entry of sapelovirus into IPEC-J2 cells is dependent on caveolae-mediated endocytosis - Zhao, Tingting (Virol J, 2019)
BACKGROUND: Porcine sapelovirus (PSV), a species of the genus Sapelovirus within the family Picornaviridae, are a significant cause of enteritis, pneumonia, polioencephalomyelitis and reproductive disorders in pigs. However, the life cycle of PSV on the molecular level is largely unknown. METHODS: Here, we used chemical inhibitors, RNA interference, and overexpression of dominant negative (DN) mutant plasmids to verify the roles of distinct endocytic pathways involved in PSV entry into porcine small intestinal epithelial cell line (IPEC-J2). RESULTS: Our experiments indicated that PSV infection was inhibited when cells were pre-treated with NH(4)Cl or chloroquine. Inhibitors nystatin, methyl-β-cyclodextrin, dynasore and wortmannin dramatically reduced PSV entry efficiency, whereas the inhibitors chlorpromazine and EIPA had no effect. Furthermore, overexpression caveolin DN mutant and siRNA against caveolin also decreased virus titers and VP1 protein synthesis, whereas overexpression EPS15 DN mutant and siRNA against EPS15 did not reduce virus infection. CONCLUSIONS: Our findings suggest that PSV entry into IPEC-J2 cells depends on caveolae/lipid raft mediated-endocytosis, that is pH-dependent and requires dynamin and PI3K but is independent of clathrin and macropinocytosis.